Adaptations in Music Lessons: Inclusion of a Student with Autism Spectrum Disorder - Sevšek, Katja; Kovačič, Bojan (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
The present research explores teaching adaptations in music education for students with Autism Spectrum Disorder (ASD) in mainstream elementary schools. We examined how teaching experience and exposure to students with ASD impact the use of inclusive strategies and teachers' self-assessed competence by conducting a structured survey of music teachers in Slovenian elementary schools. Results show that adaptation practices differ depending on teaching experience, with experienced teachers more likely to implement structured routines, quiet spaces, and environmental modifications. There is a moderate correlation between the frequency of adaptations used by teachers and their ability to identify ASD characteristics. The findings highlight the importance of practical experience and targeted training in fostering teachers' confidence and competence, as well as the need for ongoing professional development to create inclusive and supportive learning environments in music education.